Influence of the characteristics of the STM-tip on the electroluminescence spectra - Croitoru, Mihail D.; Gladilin, V. N.; Fomin, Vladimir M.; Devreese, Jozef T.; Kemerink, Martijn; Koenraad, Paulus M.; Sauthoff, Katharina; Wolter, Joachim H. (Physica. E, Low-dimensional systems & nanostructures, 2005)
We analyze the influence of the characteristics of the STM-tip (applied voltage, tip radius) on the electroluminescence spectra from an STM-tip-induced quantum dot. We find that positions of electroluminescence peaks, attributed to the electron-hole recombination in the quantum dot, are very sensitive to the characteristics of the tip, namely increasing voltage on the STM-tip results in a red shift of the electroluminescence peaks, while the peak positions as a function of the tip radius reveal a non-monotonous behavior.
Available online 24 November 2004
Gesehen am 16.12.2019